1986
DOI: 10.1128/iai.53.3.685-692.1986
|View full text |Cite
|
Sign up to set email alerts
|

Oral immunization of mice with attenuated Salmonella enteritidis containing a recombinant plasmid which codes for production of the B subunit of heat-labile Escherichia coli enterotoxin

Abstract: We used Salmonella enteritidis serotype dublin strain SL1438, a nonreverting, aromatic-dependent, histidine-requiring mutant, as a recipient for a recombinant plasmid coding for production of the nontoxic B subunit of the heat-labile Escherichia coli enterotoxin. The S. enteritidis derivative EL23 produced heat-labile enterotoxin subunit B that was indistinguishable from heat-labile enterotoxin subunit B produced by strains of E. coli or Salmonella typhi harboring the same plasmid. Mice immunized orally with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(35 citation statements)
references
References 28 publications
0
35
0
Order By: Relevance
“…Unlike most antigens given orally, administration of LT-B in this manner results in the formation of a significant intestinal antibody response. 25 Furthermore, following administration of this antigen, we found that IL-13 mRNA expression in the mesenteric lymph 5). Twenty hours after administration, RNA was extracted from the mesenteric lymph nodes of each animal; 200 ng of poly A + RNA were reverse transcribed, and then 20% of each cDNA was amplified by PCR using primers specific for IL-12p40 (a), IL-13 (b) or glyceraldehyde 3-phosphate dehydrogenase (G3PDH) (c).…”
Section: Reduction Of Primary and Secondary Intestinal Iga Anti-lt-b mentioning
confidence: 83%
See 2 more Smart Citations
“…Unlike most antigens given orally, administration of LT-B in this manner results in the formation of a significant intestinal antibody response. 25 Furthermore, following administration of this antigen, we found that IL-13 mRNA expression in the mesenteric lymph 5). Twenty hours after administration, RNA was extracted from the mesenteric lymph nodes of each animal; 200 ng of poly A + RNA were reverse transcribed, and then 20% of each cDNA was amplified by PCR using primers specific for IL-12p40 (a), IL-13 (b) or glyceraldehyde 3-phosphate dehydrogenase (G3PDH) (c).…”
Section: Reduction Of Primary and Secondary Intestinal Iga Anti-lt-b mentioning
confidence: 83%
“…Mice were killed 21 days following primary immunization with LT-B or 10 days following secondary immunization with LT-B and sera and mucosal samples were taken. Intestinal samples containing IgA were obtained as previously described 25 by homogenization (Tissuemizer, Tekmar, Cincinnati, OH) of the small intestines in 50 mM EDTA containing 0 . 1 mg soybean trypsin inhibitor.…”
Section: Determination Of Intestinal and Serum Anti-lt-b Titresmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same way, the diversity of strategies incorporating and exploiting both the natural and contrived characteristics of bacterial invasion and their diverse and tractable genetic features offers much potential in the generation of a vaccine delivery platform. In similar fashion to the delivery of eukaryotic expression vectors as DNA vaccines (notably with the potential for oral delivery), the use of attenuated Salmonella for delivery of a recombinant plasmid encoding for the non-toxic B subunit of E. coli LT was shown in-vivo for the purposes of vaccination by Clements et al (1986). Oral immunization of mice showed progressively increasing mucosal and serum antibody responses to both the E. coli LT subunit and the lipopolysaccharide (LPS) of the vaccine strain, together with the mucosal production of neutralizing IgA.…”
Section: Mucosal Immune Responsesmentioning
confidence: 99%
“…Live attenuated Salmonella strains were first developed as vaccines to prevent disease caused by Salmonella infections in humans and animals (Germanier & Fuer, 1975;Stocker et al, 1983;Hassan & Curtiss, 1990). Subsequently, genetically modified attenuated Salmonella strains were constructed for delivery of heterologous antigens (Formal et al, 1981;Clements et al, 1986;Nakayama et al, 1988). Orally administered Salmonella vaccines offer a variety of advantages over traditional vaccines, including stimulation of both systemic and mucosal responses, which are important for protection against pathogens such as plague, needle-free delivery, and a relatively low cost of production .…”
Section: Introductionmentioning
confidence: 99%